A renewable, flexible and robust single layer nitrogen-doped graphene coating Sn foil for boosting formate production from electrocatalytic CO2 reduction. (October 2019) - Huang, Jianzhi; Guo, Xinrong; Wei, Yubo; Hu, Qiong; Yu, Xiongtao; Wang, Lishi
Graphical abstract: Highlights: A general method is developed to improve Sn foil for CO2 electroreduction. A renewable and flexible SL-NG@Sn foil is designed for boosting formate production. An interesting transformation of reaction mechanism is observed at SL-NG@Sn foil. The SL-NG@Sn foil outperforms other reported Sn nanoparticles-based catalysts. Abstract: Herein, we develop a general method to stabilize and improve the electrochemical performances of commercial bulk Sn foil by coating single layer nitrogen-doped graphene (SL-NG@Sn foil) for electroreduction of CO2 to formate. The maximum Faradaic Efficiency (FE) for formate attained by SL-NG@Sn foil is 92.0% at −1.0 V (vs. RHE) in 0.5 M KHCO3 with high formate partial current density of 21.3 mA cm −2, outperforming other reported Sn nanoparticles-based catalysts. The SL-NG@Sn foil displays good flexibility, which achieve similar performance after folding. It also possesses good renewable ability that can be recycled used after simply washing with water for three usages with FE above 90%. An interesting transformation of reaction mechanism to higher kinetic activity is observed at SL-NG@Sn foil, demonstrating the synergistic effect exists between SL-NG and Sn foil.